A comparison of bird‐feeding practices in the United States and Canada. (14th May 2013) - Horn, David J.; Johansen, Stacey M.
ABSTRACT Millions of Americans and Canadians participate in the feeding of wild birds. We surveyed hobbyists about their bird‐feeding experience, and examined demographic and regional differences in responses, to determine the types of bird‐feeding practices taking place and to identify themes important for wildlife managers to communicate with people who feed birds. Between autumn 2005 and winter 2008–2009, we recruited a non‐random sample from the interested public though both print and electronic media. We had 1, 291 individuals from 48 states (USA) and 7 Canadian provinces who completed our mail and website survey. Survey respondents were primarily female (67%) and ≥45 years old (77%). Most respondents offered alternative foods in addition to traditional bird seed (≥82%) and provided other resources besides food to attract birds (≥75%). Our respondents fed birds because it brought nature (84%) and accompanying sound (81%) to the area, as a hobby (79%), and to help the birds (79%). Respondents felt attracting more bird species (69%), a greater number of birds (41%), and no pests (35%) would make their bird‐feeding experience more satisfying. Given the interested public's desire to increase bird diversity at their feeders and to help birds, managers have the opportunity to develop messages promoting habitat enhancement in addition to feeding, and provide suggestions for reducing the risk of disease transmission and pest species at feeders. © 2013 The Wildlife Society.